Fiscal Sustainability in Cross-Dependent Panels: Evidence from the German L nder - Ekkehard Köhler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper provides new evidence on the sustainability of public finances in German states (Laender) by exploiting a newly compiled database covering the years 1950-2011. Unlike previous studies on Germany, we analyze fiscal sustainability by applying second generation panel cointegration techniques. A unique identification strategy for the selection of sub-panels improves the robustness of panel cointegration tests and reveals that Laender finances are hardly sustainable.
Keywords: H72; H77; C55; 330